Critical thinking, real life problems and feedback in the sciences classroom - Carvalho, Carolina; Fiuza, Edite; Conboy, Joseph; Fonseca, Jesuína; Santos, João SANTOS; Gama, Ana Paula; Salema, Maria Helena (Journal of Turkish Science Education, 2015)
This descriptive and interpretative study was aimed at better understanding how to foment effective feedback in the sciences classroom by implementing an activity based in a real-life problem that was intended to promote critical thinking. Eleven secondary and pre-secondary public school teachers participated in a workshop in the Greater Lisbon area (part of a year-long continuing education project). In one three-hour session, they performed an activity intended to promote critical thinking, based on a real-life problem, and received feedback from a workshop facilitator. Participants responded to two questionnaires concerning the nature of the activity performed and the feedback perceived. Interpretative analysis of responses indicates that the activity performed was perceived as a real-life problem and the feedback was perceived as effective. The outcomes and conclusions contribute to a possible understanding of how such an activity can facilitate effective feedback in the sciences classroom.
Keywords: Feedback; Teacher Education; Critical Thinking; Real Life Problems